Internalization of Islamic Moderation Value in Mathematics Problem Solving - Muhammad Ilman Nafi'an; Bagus Ahmadi; Muhammad Ngizzul Muttaqin; Dian Septi Nur Afifah (CV. Media Digital Publikasi Indonesia, 2023)
Several studies have discussed the internalization of Islamic values in mathematics, including Islam and mathematics, internalization of Islamic values in mathematics learning with analogy strategies, mathematical analysis of the philosophy of the Quran, the secret of numbers in the Qur’an. However it has never been discused abaout the internalization of Islamic moderation values in mathematical problem solving. So this research is needed. Moreover, the phenomenon of Islam in Indonesia is currently shifting away from the image of moderate Islam and into a harsher conservative ideology. This is more worrying because it has entered the realm of education. For that it is necessary to internalize the value of Ilamic moderation in mathematical problem solving. One of the strategies that can be done to instill religious moderation values in mathematical problem solving is the analogy strategy. Facts, concepts, and principles in mathematics can be used a analogy to instill religious moderation values. In this study, describe some examples of the application of analogy strategies for internalizing Islamic value. This study uses the library method. The data obtained were publications of research artcles in scientific journals. The analyed articles include three stages, organizing, synthesizing and identifying. The results of data analysis show that the value of tasamuh in mathematics learning can be done through open ended problem solving. The characteristics of open ended problem is problem that have more than one solution and answer tolerance, so each student may have different and equally correct solutions and answers. This is in accordance with the principle of tasamuh value in Islamic moderation. Therefore, on classroom learning, the values of tasamuh can be implemented through open ended problem.